2017
DOI: 10.1097/jcp.0000000000000710
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole Once-Monthly in the Treatment of Acute Psychotic Episodes in Schizophrenia

Abstract: BackgroundLong-acting injectable antipsychotics are treatment options for acute and long-term treatment of patients with schizophrenia. In a previously published 12-week randomized, double-blind, placebo-controlled clinical trial of patients with schizophrenia experiencing an acute psychotic episode, aripiprazole once-monthly 400 mg (AOM 400) produced significantly greater improvement than placebo on the primary endpoint, Positive and Negative Syndrome Scale (PANSS) total score at week 10.MethodsTo examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…These favourable clinical outcomes during the 12-month study were observed despite the fact that at the time of recruitment, patients were relatively stable, although only a small proportion were in full remission. This is in line with recently published studies showing AOM to be efficacious across the spectrum of schizophrenia symptoms [30] and also observed in studies conducted with other atypical antipsychotics [31]. This could also be related to the fact that LAI medication assures adherence as long as the patient is receiving the injection.…”
Section: Discussionsupporting
confidence: 90%
“…These favourable clinical outcomes during the 12-month study were observed despite the fact that at the time of recruitment, patients were relatively stable, although only a small proportion were in full remission. This is in line with recently published studies showing AOM to be efficacious across the spectrum of schizophrenia symptoms [30] and also observed in studies conducted with other atypical antipsychotics [31]. This could also be related to the fact that LAI medication assures adherence as long as the patient is receiving the injection.…”
Section: Discussionsupporting
confidence: 90%
“…AOM 400 was significantly more effective vs placebo in improving PANSS total score, positive and negative subscale scores, and CGI-S score from baseline, with significant differences achieved at every post-baseline timepoint. The present results are confirmed by an analysis showing a significant benefit of AOM 400 across the range of PANSS Marder factors 32. Our analysis of efficacy results in Study 291 stratified by patient age (adults aged ≤35 years or >35 years) provides some insights on the effect of age on the pattern of symptom improvement after initiation of AOM 400.…”
Section: Discussionsupporting
confidence: 81%